2019
DOI: 10.1007/s12576-019-00690-9
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol 12-myristate 13-acetate (PMA) suppresses high Ca2+-enhanced adipogenesis in bone marrow stromal cells

Abstract: We have previously reported that increased extracellular and intracellular Ca 2+ lead to adipocyte accumulation in bone marrow stromal cells (BMSCs). However, strategies to suppress high Ca 2+-enhanced adipocyte accumulation have not been reported. We examined the effects of the diacylglycerol analog phorbol 12-myristate 13-acetate (PMA) on proliferation and adipogenesis of mouse primary BMSCs. We used 9 mM CaCl 2 and 100 nM ionomycin to increase extracellular Ca 2+ and intracellular Ca 2+ , respectively. PMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, there are still some studies with different results. Hashimoto et al (2019) found that phorbol 12‐myristate 13‐acetate suppressed adipocyte differentiation but enhance the proliferation of bone marrow stromal cells (BMSCs). A study about DNA (cytosine‐5)‐methyltransferase 3A also indicated that methylation of PPARγ promoter could decrease lipid accumulation, and methylation of p21 promoter promoted cell proliferation in porcine intramuscular preadipocytes (Qimuge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are still some studies with different results. Hashimoto et al (2019) found that phorbol 12‐myristate 13‐acetate suppressed adipocyte differentiation but enhance the proliferation of bone marrow stromal cells (BMSCs). A study about DNA (cytosine‐5)‐methyltransferase 3A also indicated that methylation of PPARγ promoter could decrease lipid accumulation, and methylation of p21 promoter promoted cell proliferation in porcine intramuscular preadipocytes (Qimuge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are considered to be the ideal candidate in regenerative medicine [31,38]. They hold unique characteristics that place them at the top of cell therapy pyramid, including their ability to differentiate into various cell lineages; they release many cellular regulatory cytokines [6,17,39,52], and they are able to migrate to the site of injury and use their self-renewal capacity [39]. These especially distinct traits intrigue great interest in MSCs for clinical purposes which have been translated currently by having huge number of clinical studies [25,27,37,41,45].…”
Section: Introductionmentioning
confidence: 99%